K KEBIJAKAN MONETER INDEPENDEN MENURUT IBNU KHALDUN DAN RELEVANSINYA TERHADAP STABILITAS EKONOMI INDONESIA - Nurul Rahmania; Syamsuri; Setiawan Bin Lahuri (Ekonomi Islam, 2022)
As the holder of the highest power, the government certainly has a series of strategies to design and realize the welfare of its people. The policies and development methods implemented are aimed at regulating and maximizing the country's economy. The government's role in the country's economy is realized through money spending policies and maintaining exchange rate stability. Therefore, exchange rate stability is very important in achieving price stability and the financial system. According to Ibn Khaldun, the government can make gold and silver the standard of value for money and monetary measures, so that they will be consistent in determining the price of money. Ibn Khaldun emphasized that if the economic system in a country is good and tries to maintain financial stability, it will have an impact on the existence and development of that country Keywords: Monetary Policy, Islamic Economics, Ibn Khaldun.